A review of the genus Brachysira in Ireland with the description of Brachysira praegeri and Brachysira conamarae, new raphid diatoms (Bacillariophyceae) from high status waterbodies - Kennedy, Bryan; Allott, Norman (Phytotaxa, 2017)
The genus Brachysira is frequently encountered in the algal flora of oligotrophic freshwaters. In order to re-evaluate its diversity in Irish waters, light and scanning electron microscopy was used to examine populations at 209 river sites and in 85 lakes. The full range of morphological variation of all common and sometimes challenging Brachysira populations was investigated. The study revealed two new species, Brachysira praegeri sp. nov. and Brachysira conamarae sp. nov. and compared them to all closely related taxa. The study also recorded B. intermedia and B. neglectissima which are new records for Ireland. Further taxonomic clarification is required for a diatom resembling B. intermedia and the complex of taxa around the polymorphic B. microcephala. Individual Brachysira taxa differed with respect to their optima along an alkalinity-pH gradient, but the trophic requirements of all forms were comparable, suggesting that species may be merged for routine water quality assessment. Nevertheless, it is recommended that Brachysira morphotypes be enumerated separately until their taxonomy is more fully resolved and their significance for the biodiversity of epilithic communities has been clearly established.